2018
DOI: 10.22377/ijgp.v12i04.2254
|View full text |Cite
|
Sign up to set email alerts
|

Unani Formulations for Management of Diabetes: An Overview

Abstract: Diabetes is a leading cause of death. In India, total number of diabetic patients is expected to be 79.4 million in 2030. It is a multifactorial disease leading to several complications. Traditional medicines are being looked up once again for its treatment; the WHO also recommended its further investigation. In this review, these drug its pharmacological activity and its formulation in Greco-Arab or Unani Medicine in India is explored. Singledrug used in formulation with reported anti-diabetic and related ben… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…In addition, numerous studies have found that the use of antihypertensive drugs to control high blood pressure in diabetics is associated with a lower risk of AF [5]. As a result, several laboratories are undertaking research into the treatment of hypertensive diabetics and the complications associated with this association [12]. These drugs although promising are very expensive, inaccessible and have many side effects.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, numerous studies have found that the use of antihypertensive drugs to control high blood pressure in diabetics is associated with a lower risk of AF [5]. As a result, several laboratories are undertaking research into the treatment of hypertensive diabetics and the complications associated with this association [12]. These drugs although promising are very expensive, inaccessible and have many side effects.…”
Section: Introductionmentioning
confidence: 99%